2019
DOI: 10.1038/s41598-019-42112-1
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the potentials of biocompatible silver nanoparticles on human lung carcinoma A549 cells and Helicobacter pylori

Abstract: Silver nanoparticles (AgNPs) are gaining importance in health and environment. This study synthesized AgNPs using the bark extract of a plant, Toxicodendron vernicifluum (Tv) as confirmed by a absorption peak at 420 nm corresponding to the Plasmon resonance of AgNPs. The AgNPs were spherical, oval-shaped with size range of 2–40 nm as evident by field emission transmission electron microscopy (FE-TEM) and particle size analysis (PSA). The particles formed were crystalline by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 71 publications
5
28
1
Order By: Relevance
“…The antimicrobial effect of different Ag + ion formulations against H. pylori has already been demonstrated in vivo and in vitro, but few studies on the efficacy of AgNPs are present in the literature do date. Very recently, a study about the effect of biocompatible AgNPs against H. pylori MH179988 has been published (Saravanakumar et al, 2019). The authors reported a MIC of 18.14 mg/L, which is 8 to 10 times higher than that found in the present study, highlighting the excellent bactericidal efficacy of SUNCs.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The antimicrobial effect of different Ag + ion formulations against H. pylori has already been demonstrated in vivo and in vitro, but few studies on the efficacy of AgNPs are present in the literature do date. Very recently, a study about the effect of biocompatible AgNPs against H. pylori MH179988 has been published (Saravanakumar et al, 2019). The authors reported a MIC of 18.14 mg/L, which is 8 to 10 times higher than that found in the present study, highlighting the excellent bactericidal efficacy of SUNCs.…”
Section: Discussioncontrasting
confidence: 47%
“…More in detail, AgNPs showed to be effective against H. pylori strains at very low concentrations (Amin et al, 2012(Amin et al, , 2014Gurunathan et al, 2015;Saravanakumar et al, 2019). They have also been tested on a large number of continuous and immortalized human cell lines in order to define their cytotoxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…6 b ). Furthermore, it is stated that AgNPs initiate the cell apoptosis in various cancer cell lines such as human lung carcinoma A549, HepG2, human breast cancer cell MCF‐7, HCT116 [51].…”
Section: Resultsmentioning
confidence: 99%
“…The primary requirement for the in vivo applications is the biocompatibility of AgNPs with the cells. AgNPs synthesized using Toxicodendron vernicifluum aqueous bark extract were observed to be biocompatible to mouse embryo fibroblast cell line (NIH3T3 cells) at various concentrations [139]. Althaea officinalis leaf extract synthesized AgNPs were tested for genotoxicity evaluation in vivo on Zebra-fish (Danio rerio).…”
Section: Other Biomedicalmentioning
confidence: 99%